2018
DOI: 10.7150/jbji.27348
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Elution and Mechanical Strength of PMMA Bone Cement Loaded With Borate Bioactive Glass

Abstract: Introduction: Local delivery of antibiotics using bone cement as the delivery vehicle is an established method of managing implant-associated orthopedic infections. Various fillers have been added to cement to increase antibiotic elution, but they often do so at the expense of strength. This study evaluated the effect of adding a borate bioactive glass, previously shown to promote bone formation, on vancomycin elution from PMMA bone cement.Methods: Five cement composites were made: three loaded with borate bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Bioactivity and cytotoxicity tests could be implemented, simulated body fluid could be used as the solution instead of PBS, and antibiotics could be added to see how 13‐93B3 affects their elution rate and efficacy. One study has already shown that 13‐93B3 in SmartSet MV can increase the elution rate of vancomycin from the cement (Funk et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioactivity and cytotoxicity tests could be implemented, simulated body fluid could be used as the solution instead of PBS, and antibiotics could be added to see how 13‐93B3 affects their elution rate and efficacy. One study has already shown that 13‐93B3 in SmartSet MV can increase the elution rate of vancomycin from the cement (Funk et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies added silicate‐based bioactive glasses to acrylic bone cement and then tested the composite's improved bone‐binding ability and mechanical properties (Shinzato et al, ; Shinzato et al, ). Only three times have investigators reported combining a borate‐based bioactive glass with PMMA cements: one study examined the bioactivity and osseointegration in vivo (Cui et al, ), another examined the delivery of antibiotics from the composite material (Funk, Burkes, Cole, Rahaman, & McIff, ), and the third monitored the conversion of glass to hydroxyapatite‐like precipitate (Cole, Funk, Rahaman, & McIff, ). One of our previously published studies examined the formation of a hydroxyapatite‐like layer on the surface of the composite using scanning electron microscopy and Fourier transform infrared spectroscopy (Cole et al, ), but this study did not examine the important changes in mechanical properties of the composite that occur as the glass dissolves or the rate at which it dissolves.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also found that there was a minimal drop of compressive strength between the inclusion of 0.5 g of each antibiotic and 1.0 g of each. Another study of Funk et al [ 54 ] also noted that the compressive strength of all cement composites loaded with vancomycin were higher than the weight-bearing threshold of 70 MPa with no significant difference throughout the duration of the study indicating that the elution of antibiotics does not directly affect the mechanical strength of ALBCs. Research also is being pursued to increase the recommended threshold of loaded antibiotics.…”
Section: Current State Of Antibiotic Loaded Pmma Bone Cementmentioning
confidence: 93%
“…27 Interest in bioactive borate glasses has led to many 'unique' compositions [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] such as ''1605''. [44][45][46] However, despite fundamental differences between borate and silicate glass structure, many borate compositions, including our previous work, [23][24][25][26]47 have been based on ''traditional'' silicate glass compositions like Bioglass s ''45S5'', 15,[23][24][25][26][47][48][49][50] ''13-93'', 14,16,17,[51][52][53][54][55][56][57][58][59][60][61]…”
Section: Introductionmentioning
confidence: 99%